White disadvantage: The effects of racial isolation on White pre-service teachers - Abdullah, Shakeer; Llanes , Jose; Henry, Daniel (Journal of Interdisciplinary Studies in Education, 2015)
This paper examines the preconceived attitudes toward cultural and racial diversity that pre-service teacher education students at a primarily white southern research institution bring with them to class and how those preconceptions may impact their teaching and ability to integrate into a school environment that is culturally different from their own.  Using qualitative research methods, the authors collected and analyzed written reflections from students throughout twelve sections of an educational foundation course. The authors found evidence that pre-service teachers had little understanding of the culture and behavior of African-American school children and were at a disadvantage when working with this group.